THE ROLE OF INDEPENDENT EDUCATION IN THE EDUCATION OF STUDENTS (British Journal of Global Ecology and Sustainable Development, 2024)
The article highlights the essence of directing students to independent education in technical higher educational institutions, formation of students ‘ self-development abilities, creative application of the acquired knowledge.